The impact of age and maturation on physical performance capacities in emerging adolescent surfing athletes: An argument for off-water training - Perejmibida, A.; Cripps, A.; Lyons, M.; Conlon, J. (Journal of Australian Strength and Conditioning, 2020)
The influence of age and maturation on the physical performance capacities of emerging surfing athletes are homogenous, indicating potential inefficiencies in the current physical development pathway and subsequent processes.